Upphandling av specialentreprenader på internationell marknad - Winstedt,Adam; Vilhelmsson,Roger (2015)
The purpose of the study is to find out how construction companies are affected by the hiring of foreign subcontractors. The report investigates the potential risks and what advantages and disadvantages there are construction companies to procure contracts in the international market and especially in North Europe. The work will result in a report that will have the layout of a manual regarding the procurement of foreign entrepreneurs.
Keywords: underentreprenörer; entreprenör; beställare; el; ab04; ab-u07; inköp; upphandling